Analysis of Students' Mathematical Problem-solving Ability on Number Matter - Saputra, Indra; Septiawan, Akbar; Stevano, Nandito; Marina Angraini, Lilis; Bonyah, Ebenezer (International Journal of Contemporary Studies in Education, 2025)
The ability to solve problems is very important for students to engage in the process of learning mathematics. In this study, students' ability to solve mathematical problems will be studied using Polya's indicators. The purpose of this study is to characterize the ability of grade IX Junior High School students to solve mathematical problems directly. The type of research conducted here is descriptive qualitative research. The subjects used in this study were about thirty students from State Junior High School 25 Pekanbaru for the 2023/2024 academic year in Class IX.3. Data collection was carried out by giving a validated test instrument, which was then sorted based on the mathematical problem-solving ability test scores. The data analysis technique used the Miles and Huberman model, namely data reduction, data analysis, and data estimation. The results of the analysis for each indicator of mathematical problem-solving ability reached an average of 38.325% and fell into the low category because many students solved the problem of integer material not by the stages of the indicator and errors were found in students' answers. Based on these results, it can be concluded that students' mathematical problem-solving skills are classified as weak/low.